Comparing Muscle Function of Children and Adults: Effects of Scaling for Muscle Size - Barrett, U.; Harrison, D. (Pediatric Exercise Science, 2002)
This study examined the force-velocity and power velocity relationship of the quadriceps muscles of children and adults, Measurements of muscle function were collected using the Con-Trex isokinetic dynamometer. Twenty adults and twenty children performed maximal effort knee extension at nine different velocities. The mean force-velocity curves and children and adults revealed obviious differences between the groups. The curves remained different following the corrections of torque for CSA and velocity for length. ANOVA revealed sgnificant differences in the uncorrected values of power between the two groups. When power values were corrected for lean thigh muscle volume, no significant differnces werde found in muscle strength between the groups. These findings suggest that differences in muscle strength between children and adults are a function of muscle size and imply that muscle function remains relatively unchanged from childhood to early adulthood.